2021
DOI: 10.1609/aaai.v35i1.16132
|View full text |Cite
|
Sign up to set email alerts
|

Physics-Informed Deep Learning for Traffic State Estimation: A Hybrid Paradigm Informed By Second-Order Traffic Models

Abstract: Traffic state estimation (TSE) reconstructs the traffic variables (e.g., density or average velocity) on road segments using partially observed data, which is important for traffic managements. Traditional TSE approaches mainly bifurcate into two categories: model-driven and data-driven, and each of them has shortcomings. To mitigate these limitations, hybrid TSE methods, which combine both model-driven and data-driven, are becoming a promising solution. This paper introduces a hybrid framework, physics-inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 12 publications
0
19
0
Order By: Relevance
“…Many recent studies have proposed to integrate physics-based modeling approaches with state-of-the-art deep learning techniques, giving birth to a field called "Physics-Guided Deep Learning". One can introduce additional physics-based penalty in loss function of neural networks (Shi, Mo, and Di 2021). Some efforts also lie in combining physics-based models with deep learning.…”
Section: Related Workmentioning
confidence: 99%
“…Many recent studies have proposed to integrate physics-based modeling approaches with state-of-the-art deep learning techniques, giving birth to a field called "Physics-Guided Deep Learning". One can introduce additional physics-based penalty in loss function of neural networks (Shi, Mo, and Di 2021). Some efforts also lie in combining physics-based models with deep learning.…”
Section: Related Workmentioning
confidence: 99%
“…Tis problem has both a physics-informed neural network and a physicsuninformed neural network. Whereafter, [5] proposed a hybrid framework, a physics-informed deep learning model, to combine second-order trafc fow models and neural networks for the TSE. And they used experiments to demonstrate the proposed model in terms of data efciency and estimation accuracy.…”
Section: Hybrid Of Trafc Flow Models and Neural Networkmentioning
confidence: 99%
“…Te methods of estimating trafc conditions can be briefy divided into two main approaches: model-driven and datadriven. References [4,5] have defned the data-driven method to infer trafc states based on the dependence learned from historical data using statistical or machine learning methods, such as convolutional neural networks (CNN), and long-term memory (LSTM) [6]. Te modeldriven approach is based on a priori knowledge of trafc dynamics, usually described by a physical model, e.g., the Lighthill-Whitham-Richards (LWR) models [7,8], and the cell transmission model (CTM) [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hybrid methods combine desirable features from both model-driven and data-driven approaches in order to ensure accurate results and reduce data requirements [27], [28]. A new framework in the deep learning literature, namely physics-informed deep learning, has gain significant attention the past few years with promising results as these physics-informed regularisers reduce the space of feasible solutions and approximate solutions that are consistent with the chosen models using a limited amount of data (see for example, [29], [30], [31], [32]). Despite the recent success of physics-informed learning some studies have shown that such methods might fail to train [33] or could be computationally expensive [34].…”
Section: Introductionmentioning
confidence: 99%